2018
DOI: 10.1097/01.nep.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Self-Directed Learning Readiness and Time Management Skills in Turkish Undergraduate Nursing Students

Abstract: Level of self-directed learning and academic achievement were higher in students who managed their time well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
4
20
0
6
Order By: Relevance
“…This result suggests that good time management practices, good organization of study time and leisure time activities can improve academic performance. Similar results were found in the literature (Ertuğ & Faydalı, 2018;Khaliq et al, 2019). However, in another study, there was no significant difference between students' time management skills and academic achievement scores (Eid et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result suggests that good time management practices, good organization of study time and leisure time activities can improve academic performance. Similar results were found in the literature (Ertuğ & Faydalı, 2018;Khaliq et al, 2019). However, in another study, there was no significant difference between students' time management skills and academic achievement scores (Eid et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have investigated the relationship between time management and academic performance, SE beliefs (Kader & Eissa, 2015;Ertuğ & Faydalı, 2018). However, in Turkey no study has found to determine the relationship between nursing/midwifery students' TMS, AAA and SE levels.…”
mentioning
confidence: 99%
“…10 Students who got a higher level of SDLR managed their time well and their academic achievement was also better. 11 This study aimed to finding the relationship between SDLR, study attitude, and self-efficacy. Through this study, we suggest undergraduate students to be ready for their SDL, stay positive, and improve indicated that they strongly disagreed to strongly agree.…”
Section: Self-directed Learning Readiness Scale (Sdlrs) For Nursing Educationmentioning
confidence: 99%
“…Besides, learning readiness is proven to influence learning achievement. Ready students will set a particular target and establish clear time management to reach the targets (Dangol & Shrestha, 2019;Ertuğ & Faydali, 2018).…”
Section: Learning Readinessmentioning
confidence: 99%